Evaluación del extracto acuoso a base de semillas de higuerilla (ricinus communis l.) como método de control de nematodos en tomate (solanum lycopersicum l.) bajo condiciones de laboratorio. - Chimba Taipe, William Stalin (2020)
Root nodulating nematodes, especially those of the genus Meloidogyne, are considered the most important phytoparasites because of their impact on economically important crops. In the study was evaluated the effectiveness of aqueous extract based on seeds higuerilla (R. communis L.) as a control method for tomato nematodes (S. lycopersicum L.) under laboratory conditions. For the methodology it was esed nodular root samples that were collected in greenhouses planted with tomatoes. To obtain the aqueous extract, it was applied the protocol described by (López, 2011) and (Sabillón and Bustamante, 1995) in addition to the modifications suggested by (Quimbiulco and Chimba 2019) were tested and validated in this investigation. For the extraction of nematodes it was applied the protocol described by (Pérez, 2017) in addition to the modifications suggested by (Quimbiulco and Chimba 2019), were taked into account and they were tested and validated inside of this research....